Modeling and analysis of IEEE 1609.4 MAC in the presence of error-prone channels - Akram A. Almohammedi; Nor K. Noordin; A. Sali; Fazirulhisyam Hashim; Waheb A. Jabbar; Sabri Saeed (Institute of Advanced Engineering and Science, 2019)
Vehicular Ad Hoc Networks (VANETs) have been developed to improve the safety, comfort and efficiency of driving on the road. The IEEE 1609.4 is a standard intended to support multi-channel in VANETs. These channels include one control channel for safety applications and six service channels for service applications. However, there is still no comprehensive analysis for the average delay and system throughput of IEEE 1609.4 MAC in VANETs considering error-prone channel under non-saturated conditions. In this paper, we propose an analytical models based on 1-D and 2-D Markov chain to evaluate the performance analysis of IEEE 1609.4 MAC in the presence of error-prone channels. Besides, freezing of the back-off timer is taken into consideration to provide an accurate estimation of access to the channel. The simulation results have been carried out to validate the analytical results of our model. The results show that the performance of our model outperforms the existing model in terms of packet delivery ratio and average delay of safety packets over CCH, and system throughput of service packets over SCHs.